2016
DOI: 10.1111/jphd.12159
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and periodontal disease among U.S. pregnant women and nonpregnant women of reproductive age, National Health and Nutrition Examination Survey, 1999–2004

Abstract: Objectives This study assessed and compared the prevalence and severity of dental caries and the prevalence of periodontal disease among pregnant and nonpregnant women of reproductive age (15–44 years) using data from the National Health and Nutrition Examination Survey, NHANES (1999–2004). Methods Estimates were derived from a sample of 897 pregnant women and 3,971 nonpregnant women. Chi-square and two-sample t-tests were used to assess differences between groups stratified by age, race/ethnicity, education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 25 publications
3
53
0
6
Order By: Relevance
“…This study found that a lower level of education (up to elementary school) and severe stress were significant risk factors for PD in rural areas. Many previous studies have also found that the risk of PD is inversely correlated with the level of education, and that stress and psychological factors such as depression, anxiety, and emotional and work stress are potential risk indicators or risk factors for PD . Excessive stress not only exerts an indirect negative effect when combined with smoking and alcohol intake, but also reportedly leads directly to physiological changes in the periodontium .…”
Section: Discussionmentioning
confidence: 98%
“…This study found that a lower level of education (up to elementary school) and severe stress were significant risk factors for PD in rural areas. Many previous studies have also found that the risk of PD is inversely correlated with the level of education, and that stress and psychological factors such as depression, anxiety, and emotional and work stress are potential risk indicators or risk factors for PD . Excessive stress not only exerts an indirect negative effect when combined with smoking and alcohol intake, but also reportedly leads directly to physiological changes in the periodontium .…”
Section: Discussionmentioning
confidence: 98%
“…What might explain these patterns of periodontal disease? In addition to elements of interpersonal variability, including host genetics, comorbid medical conditions, social determinants, and lifestyle and behavioral habits, the local tooth environment likely contributes to the spatial patterning of dental disease 75,76 , which is mediated in part by the microbiota.…”
Section: Spatial Patterns Of Periodontal Disease and The Subgingival mentioning
confidence: 99%
“…Within the reproductive health care cycle, the antenatal care comprises important health care functions, including health promotion, screening, diagnosis and prevention of diseases [12]. Thus, dental antenatal cares are of great relevance for promoting maternal and child health [13][14][15], since pregnant women represent a risk group for oral diseases due to their physical, biological, hormonal and behavioral changes, and the high prevalence of dental caries and periodontal diseases in pregnancy [16][17][18][19][20][21][22]. There are also indications that periodontal diseases may be associated with low-birth-weight newborns and preterm births [23,24].…”
Section: Introductionmentioning
confidence: 99%